2011
DOI: 10.1038/ncomms1460
|View full text |Cite
|
Sign up to set email alerts
|

Direct visualization of microtubules using a genetic tool to analyse radial progenitor-astrocyte continuum in brain

Abstract: Microtubule cytoskeletal dynamics of cortical progenitors and astroglial cells play critical roles in the emergence of normal functional organization of cerebral cortex and in disease processes such as tumorigenesis. However, tools to efficiently visualize these events are lacking. Here we describe a mouse genetic model to efficiently visualize and analyze radial progenitors, their astroglial progeny, and the microtubule cytoskeleton of these cells in the developing and adult brain. Using this tool, we demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…We did not observe any motility of fine astrocytic processes on the timescale of tens of minutes, suggesting that astrocytes in the adult intact brain of anesthetized animals may not be motile. This agrees with in vivo imaging of microtubule structures in astrocytic processes, which was also described to be stable on these timescales, 18 and with our time-lapse studies of the dynamics of very superficial fine processes in the BAC GLT-1 EGFP mouse. While we cannot rule out that processes that fall under our detection limit may be motile, it is interesting to note that we could visualize processes that were ∼1 μm in size, similar to the size of motile processes in previous in vitro studies of developing systems.…”
Section: Dynamics Of Astrocytic Processessupporting
confidence: 91%
See 3 more Smart Citations
“…We did not observe any motility of fine astrocytic processes on the timescale of tens of minutes, suggesting that astrocytes in the adult intact brain of anesthetized animals may not be motile. This agrees with in vivo imaging of microtubule structures in astrocytic processes, which was also described to be stable on these timescales, 18 and with our time-lapse studies of the dynamics of very superficial fine processes in the BAC GLT-1 EGFP mouse. While we cannot rule out that processes that fall under our detection limit may be motile, it is interesting to note that we could visualize processes that were ∼1 μm in size, similar to the size of motile processes in previous in vitro studies of developing systems.…”
Section: Dynamics Of Astrocytic Processessupporting
confidence: 91%
“…We did not observe any overt changes in the process arbor during this time, suggesting that astrocytic processes in anesthetized animals in vivo may be structurally stable on these timescales. 18 To compare BAC Id3 EGFP mice to other available astrocytic reporter strains, we also carried out in vivo imaging experiments on BAC GLT-1 transgenic mice, in which the majority of astrocytes throughout the brain express EGFP. 21 While astrocytes have previously been visualized in these mice using Visualization of blood vessels and astrocytes in the cortex of BAC Id3 mice in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As microtubules pull neuronal somas, they are the basic structures necessary for radial migration. 45 Previous evidence demonstrated that newborn cortical neuron motility is significantly impaired in the absence of ADAM10 and that disrupted microtubules are related to the decreased expression of acetylated tubulin and microtubule-associated proteins. 9 Intriguingly, the NICD/RBPJ complex can enhance the promoter activity of doublecortin, a modulator of microtubule cytoskeletons, and up-regulate the expression of doublecortin in neurons.…”
Section: Radial Migration and Laminationmentioning
confidence: 99%